FT–IR and FT–Raman spectroscopic investigations of adsorption of 2-aminopyridine on natural and ion-exchanged bentonites - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 1999)
The adsorption of 2-aminopydine (2AP) on natural and ion-exchanged bentonites (Mn-, Fe-, Co- or Ni-bentonite) have been investigated using IR and Raman Spectroscopy. The intercalation of 2AP within natural and ion-exchanged bentonites has been shown by X-ray diffraction to increase the interlayer spacing. Vibrational spectroscopy indicates that intercalated 2AP molecules are coordinated to Lewis acid sites or exchangeable cations (directly or indirectly through water bridges). It is concluded that ring nitrogen, not the amino nitrogen is involved in coordination. Moreover amino group hydrogens are found to be involved in hydrogen bonding interaction with water molecules (NH⋯OH2).
Keywords: FT–IR; FT–Raman; Clay; Bentonite; Intercalation; Aminopyridine